The Dragon and the Tiger: Realties in the Control of Tuberculosis - P. Bhatter; A. Chatterjee; N. Mistry (Interdisciplinary Perspectives on Infectious Diseases)
India and China are two Asian super-powers with developing economies carried on the shoulders of their booming populations. This growth can only be sustained by nurturing their “human resource”. However increasing reports of insufficient public health (PH) initiatives in India when compared to the aggressive PH system of China may prove to be the Achilles’ heels for India. This review compares the PH system in India and China for combating Tuberculosis (TB), the disease responsible for maximum mortality and morbidity by a single infectious agent. While China has acknowledged the disease load and thereafter has methodically improved its reporting, detection, diagnosis and treatment, India is still in denial of the imminent health risk. The Indian PH system still considers TB as a “facultative” disease for which the required control measures are already in place and functioning. Globally, India and China recorded the highest Multi-Drug Resistant TB (MDR) cases notified in 2010 (64000 and 63000, respectively). Additionally non-government sources reported extremely high proportions of MDR in India. Here we have compared the medical, social and economic approaches of the two nations towards better management and control of TB. Does India have lessons to learn from China?